Strategic Market Segmentation for Gen Z Skincare Consumers: A Multi- Variable STP Framework Application for Pre-Launch Brand Market Entry in Indonesia's Digital Beauty Ecosystem - Mikael Bryan Ciputra; Joseph Setiawan; Brianna Sanjaya; Antonius Felix (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study applies the Segmentation–Targeting–Positioning (STP) framework to formulate a market entry strategy for L’Essaine, a pre-launch skincare brand targeting Indonesian Gen Z consumers. A multi-dimensional segmentation approach incorporating demographic, geographic, psychographic, and behavioral variables is employed to identify and evaluate potential market segments. The research adopts a qualitative design, utilizing triangulated primary data from in-depth interviews with 15 respondents aged 17–30, complemented by secondary data from industry reports and competitive analyses. The findings reveal that university students aged 17–24 with moderate monthly allowances represent an underserved yet attractive segment seeking affordable skincare products with premium quality attributes. This segment achieved an overall attractiveness score of 7.8 out of 10, indicating strong potential for market entry. Based on these findings, the study proposes an “affordable premium” positioning strategy that emphasizes the use of natural ingredients and a digital-first engagement approach aligned with Gen Z media consumption behaviors. Validation through content marketing performance indicates strong resonance with the target audience, reflected in a 3.9% engagement rate and 85% audience relevance. This research contributes to the application of the STP framework in digital-native consumer markets and provides practical strategic insights for brand entry in Indonesia’s competitive skincare industry.